Seasonal variation and mixing behaviour of glutathione, thioacetamide and fulvic acids in a temperate macrotidal estuary (Aulne, NW France). (5th January 2017) - Marie, Lauriane; Pernet-Coudrier, Benoît; Waeles, Matthieu; Riso, Ricardo
Abstract: Fulvic acids and two dissolved reduced sulphur substances (RSS) were analysed for one year along the whole salinity gradient in the Aulne estuary (north-western France) using differential pulse cathodic stripping voltammetry. Concentrations of glutathione-like (GSH-like), thioacetamide-like (TA-like) and fulvic acid-like (FA-like) compounds ranged from 0.2 to 38 nmol L −1, from 0.02 to 6.6 μmol L −1 and from 0.1 to 4 mgC L −1, respectively. Our results indicated primarily allochthonous-continental sources for all three compounds. The behaviour of GSH-like compounds along the salinity gradient was globally conservative, with minor losses (<25%), possibly limited due to metal complexation. TA-like compounds generally displayed non-conservative behaviour with important removals. In terms of the TA-like budget, losses were counterbalanced by exceptional inputs occurring in the flood period (February). FA-like compounds were intensely degraded (∼50%) in the last section of the river and then behaved conservatively in the estuary. The annual flux of FA-like compounds to coastal waters was 2800 ± 600 tC. This flux was mainly (74%) delivered during the high discharge period, in accordance with its known pedogenic origin. Graphical abstract: Highlights: Reduced sulphur substances and fulvic acids were analysed across an estuary over one year. An allochthonous-continental source was evidenced for all compounds. Glutathione was not removed in the estuary, perhaps due to metal complexation. Removals of thioacetamide were counterbalanced by high inputs in flood period. Fulvic acids were mainly exported during the rainy period and behaved conservatively.